A new view to pun in khaghani âs odes as a style characteristic - Mohsen Hoseini; Javad Mortezaei (مطالعات زبانی و بلاغی)
Paying  too much attention to rhetorical figures is one of the charecteristics of in addition to khaghani ‘s works  that are the best example of this style they include all of the characteristic which shows his personal style . Pun as one of the rhetorical figures is one of the highest  frequencies in rhetorical figures used in khaghani’s odes that can be one of the characteristic  of his personal style and it includes different types : 1 . Pun Imaging           2 . pictured pun        3 . functional pun in picture making 4 . pun mlfvf                        5 . pun following  features of involution and evolution 6 . absolute pun with convention of rejection and   reverse 7 . dependent and conjugate pun